Spatial Analysis of Soybean and Sugarcane Monocultures in the Goiás Landscape - Santana, Beatriz da Silva Feitoza; Amaral, Felipe Gonçalves; Cruz, Carla Bernadete Madureira (Anuário do Instituto de Geociências, 2022)
Goiás represents Brazil as one of the most important states in agricultural production. 97% of this territory is located in the Brazilian Cerrado, an area of fundamental importance for the understanding of agriculture. The relevance of soy is closely linked to its market value, being present since the 1970s and dominating Brazilian territory, becoming popular as the main export product. Sugar cane, on the other hand, reflects the mosaic of cultures and the recent economy of Goiás. This crop presents a progressive growth based on the interest for its derivatives (ethanol and sugar) and the expansion of the sugar-energy sector in the country. This paper intends to analyze the spatiotemporal behavior of soybean and sugarcane crops in the state of Goiás between the years 1988 to 2018, using geotechnologies. The two cultures present a favorable situation and confirmed the hypotheses brought throughout the work. The use of different forms of representation and analysis aided in the understanding the South of Goiás, a mesoregion that stands out for both crops. The two cultures dominate almost entirely the Goiás lands destined for agricultural production, however, the spatial-temporal dynamics of each one of them occurs in different ways and at different times.